The Role of Xylitol Gum Chewing in Restoring Postoperative Bowel Activity After Cesarean Section. (March 2016) - Lee, Jian Tao; Hsieh, Mei-Hui; Cheng, Po-Jen; Lin, Jr-Rung
Aims: The goal of this study was to evaluate the effects of xylitol gum chewing on gastrointestinal recovery after cesarean section. Methods: Women who underwent cesarean section ( N = 120) were randomly allocated into Group A (xylitol gum), Group B (nonxylitol gum), or the control group (no chewing gum). Every 2 hr post-cesarean section and until first flatus, Groups A and B received two pellets of chewing gum and were asked to chew for 15 min. The times to first bowel sounds, first flatus, and first defecation were then compared among the three groups. Results: Group A had the shortest mean time to first bowel sounds (6.9 ± 1.7 hr), followed by Group B (8 ± 1.6 hr) and the control group (12.8 ± 2.5 hr; one-way analysis of variance, p < .001; Scheffe's post hoc comparisons, p < .05). The gum-chewing groups demonstrated a faster return of flatus than the control group did ( p < .001), but the time to flatus did not differ significantly between the gum-chewing groups. Additionally, the differences in the time to first defecation were not significant. Conclusion: After cesarean section, chewing gum increased participants' return of bowel activity, as measured by the appearance of bowel sounds and the passage of flatus. In this context, xylitol-containing gum may be superior to xylitol-free gum.